A numerical model on geosynthetic reinforced pile supported embankments - Balaban, Eren; Onur, Mehmet İnanc (My University, 2018)
Reinforced pile embankments are started use more commonly because they allow fast construction of highways. When geosynthetics are adopted to piled fills, this kind of structures are then called as geosynthetic reinforced piled structures. When the geosynthetics are used, area of pile caps is reduced because geosynthetic transfers fill load to piles by its membrane effect. In this study, effect of multi – layer reinforcement is investigated using 2D finite element method. For this purpose, settlements, pressures, excess pore water and horizontal displacements are analyzed. Results showed that using two and three layers of reinforcement significantly decreases settlements on foundation soil and embankment surface. Placement of additional layer has great effect on settlements, pressures, excess pore water pressure and horizontal displacements. It is also found out that, two layers of reinforcement is more effective when only settlements are considered.
A numerical model on geosynthetic reinforced pile supported embankments
Keywords: Geosynthetic Reinforced Pile Supported Embankment; Settlement; Pile; Stress Distribution; Geosynthetic Reinforced Pile Supported Embankment; Settlement; Pile; Stress Distribution